Sectoral and regional allocation of foreign direct investment in Mexico The impact of NAFTA and EU-MEXICO Free Trade Agreements. - Chaparro, Jorge; Daza Aramayo, Lourdes Gabriela, 1983-; Chvalkovská, Jana; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This thesis analyze the economic development and FDI prospects in the context of the Free Trade Agreements that Mexico has signed in the context of NAFTA with the United States and Canada, as well as EU-MEXICO FTA with the European Union. The analysis will be focused around the regional allocation of FDI, the analysis of the main industrial sectors where FDI lands and on the most active foreign investors in the country. However, a new series of reforms and measures to advance liberalization have triggered the interest of other countries to invest in Mexico; Most notably, from Europe. These new FDI inflows are being allocated in different regions and shifting away from manufacturing industries into the service sectors and on to new investment opportunities in strategic industries.
Vedoucí práce: Lourdes Gabriela Daza Aramayo
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses